Study of Pap Smear as Cervical Cancer Screening: A Prospective Study at a Periurban Tertiary Care Centre - Priya Pratapan (Nair); Mugdha Jungari; Mrunal Nakade; Kiran Borkar; Saunitra A. Inamdar (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Cancer cervix is fourth most common cancer in the world and second most common in India. In India, cervical cancer is the leading cause of mortality and morbidity amongst women. Methodology:This prospective study was conducted among 200 women undergoing Pap Smear Test at gynecology OPD between January-June 2020. Pap smear test was classified as per Bethesda system. Result: Abnormal pap smear report was seen among 25.5% women. Higher proportion of abnormal pap report was seen among women aged 21-30 years (41.17%), with a duration of married life between 10-20 years 33.3%. The common abnormal pap smear report finding were inflammatory changes and vaginosis. Epithelial cell abnormalities were found among 18 (9%) women. Conclusion: Pap smear test is a simple, affordable, effective, and practical screening test for early detection of cervical cancer, and it decreases morbidities and mortalities due to cervical cancer.